Modelling modal shift due to the enhanced level of bus service - Vedagiri, Perumal; Arasan, Venkatachalam T. (Transport, 2009)
This study is concerned with the estimation of the probable shift of auto‐rickshaw (three wheeled motorized para‐transit vehicle) users to the bus due to an increase in its level of service after providing exclusive bus lanes on Indian city roads carrying heterogeneous traffic. The quantum of an increase in the level of bus service due to the introduction of an exclusive bus lane was determined using a recently developed simulation model of heterogeneous traffic flow. The data on other factors (variables) that might cause modal shift from the auto‐rickshaw to the bus was collected conducting a home‐interview survey based on the stated preference approach. A binary logit model of mode‐choice was then calibrated using the collected data and the model was also validated using a holdout sample. A mode‐choice probability curve to depict the possible shift of auto‐rickshaw users to the bus is developed taking difference in the travel times of two‐modes as the basis to serve as a user friendly tool to analyze the possible modal shift for a wide range of the values of the involved variables.First published online: 27 Oct 2010